Variabilidade espacial de atributos dendrométricas do eucalipto e de um neossolo quartzarênico a partir da aplicação de calcário ou lama de cal + oxyfertil - Lima, Elizeu de Souza [UNESP] (2015)
The fertilization using cellulosic waste used in eucalyptus forestry systems is a great soil conservation practice, since it provides fertilizer saving is descompactante restores good chemical, physical and biological conditions and, above all, increases the productivity of the timber, and prevents waste is deposited in inappropriate places. The objective of this study was to evaluate the spatial variability of individual productivity of Eucalyptus urograndis trees according to the attributes of a Entisol Typic soil in order to highlight specific management zones in order to use the residue of cellulose extraction as sustainably fertilizers to the environment. In 2014, in the experimental area of the Bom Retiro Farm's owned by Eldorado Celulose Brazil in the city of Três Lagoas, located in the Brazilian Cerrado conditions were installed three experimental mesh containing 50 sampling grids totaling 1 ha each experimental grid. Linear and spatial correlations were examined between the plant and the soil in order to highlight specific management areas in order to return the cellulose waste as fertilizer to sustainably environment. While the studied plant attributes were height (Hei), diameter at chest hight (DCH), and wood volume (VOL). Soil attributes were mechanical resistance to penetration (RP), gravimetric moisture (GM), sand, silt, clay, phosphorus (P), organic matter (OM), hydrogen potential (pH), potassium (K + ), calcium (Ca 2+ ), magnesium (mg 2+ ), aluminum (Al 3+ ), sum of bases (SB) and cation exchange capacity (CEC), collected from 0 to 0.20 and 0.20 to 0.40 m depth. Statistical analysis was comprised of: initial descriptive analysis of the attributes, analysis of linear correlation, spatial and temporal between them and the geostatistic analysis, in order, highlight conditions that provide increased productivity of place forests through fertilization held the cellulosic waste. The phosphorus, organic matter and ...